A Review on Ophthalmologic Manifestations in Beta-Thalassemia Major Patients - Ghaedi, Negar; Hashemian, Hesam (Journal of Ophthalmic and Optometric Sciences, 2022)
Background: Beta-thalassemia is an inherited blood disorder that leads to early apoptosis of red blood cells (RBCs), ineffective erythropoiesis, and ocular complications. The disease is classified into beta-thalassemia minor (β-TMi), beta-thalassemia intermedia (β-TI), and beta-thalassemia major (β-TM).We aim to review various functional and structural ocular manifestations of β-TM patients in different studies and present the most important findings based on the prevalence and etiologies of each ocular complication. Materials and methods: To reach this purpose, we developed a search strategy using the keywords “eye disease,” “ocular complications,” “ocular manifestations,” and “ocular abnormality,” each with “beta-thalassemia” in the two popular search engines PubMed and Google Scholar up to December 2022. We also reviewed related references of the chosen papers. Results: According to the literature review, the most consistent is the correlation of β-TM with dry eye disease and fundus alterations, while there are still many challenges regarding the prevalence and etiologies of other ocular complications in β-TM patients. Conclusion: This finding warrants studies with larger sample sizes to reach more reliable results and take them into action for preventing and timely diagnosing such ocular complications.